Hexyltrimethylammonium Bromide Solutions at 278.15: A Dielectric Investigation on Micelle Relaxation and Hydration - N., Rohman; T., Mohiuddin; I., Khan; R., Selvaraj (INTI International University, 2023)
We have examined the dielectric relaxation of hexyltrimethylammonium bromide solutions at 278.15 K and at 298.15 K in order to investigate the impact of hydrophobic and hydrophilic hydration on temperature. The dynamics of micelles and their hydrophilic and hydrophobic hydration of n-hexyltrimethylammonium bromide solutions are investigated at a low temperature of 278.15 K using dielectric measurements. The concentration ranged from 0.0982 to 0.8534 mol•dm-3, and the frequency range covered from 0.2 to 89 GHz. Four Debye processes added together fit all the spectra. Micelle relaxation processes are visible below the critical micelle concentration, which denotes premicellar aggregation. The relaxation mechanisms were investigated with the aid of Grosse's hypothesis. Due to the radial and tangential diffusion of unbound and bound counter ions around the charged micelles, the two low frequencies are consequently ascribed to these processes. The hydrophilic hydration, in which the water molecules are entirely immobilised, is shown to be temperature independent. On the other side, at lower temperatures, the hydrophobic hydration rises